2010
DOI: 10.1074/jbc.m110.158295
|View full text |Cite
|
Sign up to set email alerts
|

Selective Yolk Deposition and Mannose Phosphorylation of Lysosomal Glycosidases in Zebrafish

Abstract: The regulation and function of lysosomal hydrolases during yolk consumption and embryogenesis in zebrafish are poorly understood. In an effort to better define the lysosomal biochemistry of this organism, we analyzed the developmental expression, biochemical properties, and function of several glycosidases in zebrafish eggs, embryos, and adult tissues. Our results demonstrated that the specific activity of most enzymes increases during embryogenesis, likely reflecting a greater need for turnover within the emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
(27 reference statements)
4
18
0
Order By: Relevance
“…4 Furthermore, we have established the senescence-associated Glb1/b-galactosidase (SA-Glb1) assay, which is commonly used to monitor senescence in mammalian cells, in zebrafish embryos and larvae as well as adults. 4,7,[15][16][17] The appearance of yolk opaqueness accompanied by increased SA-Glb1 activity in spns1-mutant fish embryos or larvae supports the notion that the interruption of the intrinsic nutrient supply, supposedly from autophagydependent catabolism of the yolk in zebrafish embryos and larvae, 18 may lead to profound energetic exhaustion under the aberrant autolysosomal condition resulting from Spns1 deficiency. As reported previously, we found that a specific inhibitor of the v-ATPase, bafilomycin A 1 (BafA), and several other U.S. Food and Drug Administration-approved proton-pump inhibitors such as omeprazole, lansoprazole and pantoprazole could significantly suppress the phenotypes induced by Spns1 deficiency ( Fig.…”
Section: Chemical and Genetic Modulations Of V-atpase In Spns1-deficimentioning
confidence: 61%
“…4 Furthermore, we have established the senescence-associated Glb1/b-galactosidase (SA-Glb1) assay, which is commonly used to monitor senescence in mammalian cells, in zebrafish embryos and larvae as well as adults. 4,7,[15][16][17] The appearance of yolk opaqueness accompanied by increased SA-Glb1 activity in spns1-mutant fish embryos or larvae supports the notion that the interruption of the intrinsic nutrient supply, supposedly from autophagydependent catabolism of the yolk in zebrafish embryos and larvae, 18 may lead to profound energetic exhaustion under the aberrant autolysosomal condition resulting from Spns1 deficiency. As reported previously, we found that a specific inhibitor of the v-ATPase, bafilomycin A 1 (BafA), and several other U.S. Food and Drug Administration-approved proton-pump inhibitors such as omeprazole, lansoprazole and pantoprazole could significantly suppress the phenotypes induced by Spns1 deficiency ( Fig.…”
Section: Chemical and Genetic Modulations Of V-atpase In Spns1-deficimentioning
confidence: 61%
“…To assess the M6P levels on Ctsk, WT and MLII embryonic lysates were passed over a cation-independent M6P receptor (CI-MPR) affinity column and Ctsk activity from the bound and unbound fractions assessed. (38) As shown in Supplemental Table S1, 86% of the Ctsk activity and 16% of the Ctsd activity from WT lysates bound the CI-MPR column. This indicates that at least one of two N-linked sugar chains on zebrafish Ctsk normally bears M6P, whereas the single sugar chain on Ctsd is minimally modified.…”
Section: Resultsmentioning
confidence: 94%
“…Because the activities of these enzymes were indistinguishable in lysates of whole WT and mutant animals (23), these data suggest that in gnptg −/− cells the majority of enzyme resides in the extracellular space. In contrast to the galactosidases, the activity of acid α-glucosidase, a lysosomal hydrolase that is not M6P modified in zebrafish (30), was similar within WT and mutant cells (Figure 2B). Additionally, the intracellular levels of two highly modified cathepsins (Ctsk and Ctsl), and the minimally modified Ctsd, were all also indistinguishable between WT and gnptg −/− sorted cells (Figure 2C–E).…”
Section: Resultsmentioning
confidence: 99%
“…To ask whether glycosidases also accumulate in the bloodstream of zebrafish, blood serum was isolated from WT and gnptg −/− adults and the activities of β-glucuronidase and β-hexosaminidase measured. Both activities were normalized to acid α-glucosidase, which was previously shown in zebrafish to lack the M6P modification (30). The absolute activity level of acid α-glucosidase was similar in serum isolated from gnptg −/− and WT adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation